Effect of Glutaraldehyde Concentration Variation toward Properties and Performance of Composite Membrane (Chi-Mmt) for DMFC Application - Sudir Umar; Dian Permana; Lukman Atmaja (IPTEK Journal of Proceedings Series, 2015)
Membrane CS/MMT-GA were synthesized by inversion phase method. In this study, CS as matrix, MMT as filler and GA as cross linking agent. CS-GA-MMT showed high performance as good candidate for DMFC. The best composition was obtained to CS/MMT-GA2 with highest proton conductivity and lower methanol permeability.